Evaluation of nutritional, phytochemical, antioxidant and cytotoxic potential of Capsella bursa-pastoris, a wild vegetable from potohar region of Pakistan - Riaz, Iqra; Bibi, Yamin; Ahmed, Nabeela (Kuwait Journal of Science, 2021)
Capsella bursa-pastoris has been analyzed for nutritional composition, antioxidant and cytotoxic potential to reveal its nutraceutical and medicinal importance. Methanol and chloroform extracts were used for preliminary phytochemical analysis following quantification of total phenolic, flavonoid, tannins, saponins and alkaloids. Antioxidant activity was determined by using DPPH, phosphomolybdate and reducing power assays. Proximate and elemental analysis was performed by using standard methods. Brine shrimp larvae assay was used to determine cytotoxicity of chloroform and methanol extract. Chloroform and methanol extract of the plant indicated presence of 156µg/mg and 128µg/ml flavonoids respectively. Plant was found to have high carbohydrate and protein contents. High level mineral composition was determined containing Potassium, Sodium, Iron, Zinc and Copper. Results of antioxidant activity by DPPH method indicated IC50 of 235.37µg/ml and 552.01 µgml-1 for chloroform and methanol extract respectively. Brine shrimp larvae assay was used to determine the cytotoxicity resulting LD50 of 246.4469 μg/ml and 169.85μg/ml of methanol and chloroform extract respectively. Study inferred that Capsella bursa-pastoriscan can serve as a good source of protein and energy as well as micronutrients in the form of a leafy vegetable for human consumption.